Social representations of alcohol and drug abuse among youth - E B Berezina; I B Bovina (Peoples' Friendship University of Russia (RUDN University), 2010)
The characteristics of representations of young people about alcohol and drug abuse are analyzed in the article. The authors reveal the key elements of the representations of alcoholism and drug abuse, discuss their differences and similarities.